Climate Risk Management in Agricultural Extension - Kenya Handbook (Nationally Endorsed Edition) - Hansen, James; Dinku, Tufa; Trzaska, Sylwia; Grossi, Amanda; Huyer, Sophia; Moore, Maya; Dinh, Dannie; Ruirie, Onesmus; Okach, Lucas; Ngari, Peterson; Murage, Paul; Kiambe, Kevin; et al. (2025)
Kenya’s agriculture, livestock, fisheries, and blue economy are increasingly threatened by climate variability and change. The Climate Risk Management in Agricultural Extension (CRMAE) Kenya Handbook (Nationally Endorsed Edition) responds to these challenges by equipping extension officers with the knowledge and tools to apply climate information in their work. Aligned with national frameworks such as the NCCAP and the Kenya National Framework for Climate Services, it strengthens the “last mile” of climate services delivery. Through multi-stakeholder collaboration, the handbook bridges policy and practice to foster climate-resilient livelihoods, sustainable food systems, and informed decision-making across Kenya’s agricultural landscape.